Validasi Metode Analisa Kadar Fenolik Ekstrak Etanol Jahe Merah (Zingiber officinale var rubrum rhizoma) dengan Spektroscopy UV-Vis - Hermawan Purba; Bonar Sinaga; Junius Gian Ginting (Program Studi S1 Farmasi, STIKES Senior, Medan, 2023)
A validation study of the phenolic content analysis method has been carried out using the Galic acid method for jahe merah. Jahe merah in this study was previously characterized microscopically and macroscopically and a filter phytochemical test was carried out to determine the content of secondary metabolites in jahe merah. Furthermore, extraction is carried out by the maceration method. The resulting extract was then analyzed to determine the phenolic content in the sample. Determination of phenolic content uses a method that has been calibrated first, which includes linearity, LOD and LOQ, precision, accuracy, and sensitivity. The results of the analysis of the analytical parameters are as follows: linearity = 0.9909, Precision = 0.046; 0.06; 0.019 recovery = 98 and 102 %, sensitivity = 1.02. 105 L. Mol-1 cm-1. Analysis of the phenolic sample of the sample showed a concentration value of 180,2 mg GAE/gram jahe extract.